2014
DOI: 10.1124/dmd.114.057190
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Exposure of Troglitazone Metabolites in Rat Sandwich-Cultured Hepatocytes Lacking Bcrp and Mrp2: Interplay between Formation and Excretion

Abstract: Inhibition of bile acid transport by troglitazone (TGZ) and its major metabolite, TGZ sulfate (TS), may lead to hepatocellular accumulation of toxic bile acids; TS accumulation and hepatotoxicity may be associated with impaired TS biliary excretion. This study evaluated the impact of impaired transport of breast cancer resistance protein (Bcrp) and multidrug resistance-associated protein 2 (Mrp2) on the hepatobiliary disposition of generated metabolites, TS and TGZ glucuronide (TG). Sandwich-cultured hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…49 The interplay between formation and excretion of TGZ metabolites was studied in rat SCH lacking Bcrp and Mrp2 by Yang et al using RNA interference techniques to knock down Bcrp in SCH prepared from TR − rats. 58 In some cases, only the metabolites are transporter inhibitors. For example, although estradiol and bilirubin do not inhibit MRP2, pre-exposure of rat SCH to estradiol and bilirubin decreased the biliary excretion of 5-(and 6)-carboxy-2′,7′-dichlorofluorescein, a MRP2 substrate, which could be attributed to the inhibition by the generated metabolites of estradiol and bilirubin.…”
Section: Use Of Sandwich–cultured Hepatocytes In Studying Drug Disposmentioning
confidence: 99%
“…49 The interplay between formation and excretion of TGZ metabolites was studied in rat SCH lacking Bcrp and Mrp2 by Yang et al using RNA interference techniques to knock down Bcrp in SCH prepared from TR − rats. 58 In some cases, only the metabolites are transporter inhibitors. For example, although estradiol and bilirubin do not inhibit MRP2, pre-exposure of rat SCH to estradiol and bilirubin decreased the biliary excretion of 5-(and 6)-carboxy-2′,7′-dichlorofluorescein, a MRP2 substrate, which could be attributed to the inhibition by the generated metabolites of estradiol and bilirubin.…”
Section: Use Of Sandwich–cultured Hepatocytes In Studying Drug Disposmentioning
confidence: 99%
“…It was suggested that both a compound’s susceptibility to glucuronidation by the UGT enzyme and the resulting glucuronide’s affinity to efflux transporter determined a compound’s susceptibility to glucuronidation in cells (63). Rat SCH lacking Bcrp (using adenoviral vectors expressing shRNA targeting Bcrp) and/or Mrp2 (from Mrp2-knockout rat) was also used previously to study the interplay between the formation of a glucuronide and its excretion by specific transporter (s) (108). …”
Section: Mechanistic Modeling Of Glucuronide Dispositionmentioning
confidence: 99%